Bioremediation a sustainable approach to preserving earth's water - Sharma, Sanjay Kumar (CRC Press, 2020)
"Bioremediation: A Sustainable Approach to Preserving Earth's Water discusses the latest research in green chemistry practices and principles that are involved in water remediation and the quality improvement of water. The presence of heavy metals, dyes, fluoride, dissolved solids and many other pollutants are responsible for water pollution and poor water quality. The removal of these pollutants in water resources is necessary, yet challenging. Water preservation is of great importance globally and researchers are making significant progress in ensuring this precious commodity is safe and potable. This volume illustrates how bioremediation in particular is a promising green technique globally"--
Keywords: Water / Purification / Biological treatment; Bioremediation; Green chemistry; Eau / Épuration / Traitement biologique; Biorestauration; Chimie verte